Conformational dynamics of bacterial and human cytoplasmic models of the ribosomal A-site - Panecka, Joanna; Šponer, Jiří; Trylska, Joanna (Biochimie, 2015)
The aminoacyl-tRNA binding site (A-site) is located in helix 44 of small ribosomal subunit. The mobile adenines 1492 and 1493 (Escherichia coli numbering), forming the A-site bulge, act as a functional switch that ensures mRNA decoding accuracy. Structural data on the oligonucleotide models mimicking the ribosomal A-site with sequences corresponding to bacterial and human cytoplasmic sites confirm that this RNA motif forms also without the ribosome context. We performed all-atom molecular dynamics simulations of these crystallographic A-site models to compare their conformational properties. We found that the human A-site bulge is more internally flexible than the bacterial one and has different base pairing preferences, which result in the overall different shapes of these bulges and cation density distributions. Also, in the human A-site model we observed repetitive destacking of A1492, while A1493 was more stably paired than in the bacterial variant. Based on the dynamics of the A-sites we suggest why aminoglycoside antibiotics, which target the bacterial A-site, have lower binding affinities and anti-translational activities toward the human variant.
Keywords: Crystallography, X-Ray; Ribosome Subunits, Small, Eukaryotic; malé podjednotky ribozomu eukaryotické; Bacterial A-site; Human cytoplasmic A-site; Ribosomal RNA; Molecular Dynamics Simulation; Aminoglycoside antibiotics; krystalografie rentgenová; simulace molekulární dynamiky; lidé; Ribosome Subunits, Small, Bacterial; Escherichia coli; malé podjednotky ribozomu bakteriální; Humans; Molecular dynamics simulations